FRI0287 The Use of A Dorsal Approach for The Injection of Botulinum Toxin A in The Treatment of Raynauds Phenomenon Secondary To Scleroderma. (15th July 2016) - Dhaliwal, K.; Griffin, M.; Salinas, S.; Howell, K.; Denton, C.; Butler, P.
Abstract : Background: Raynaud's phenomenon (RP) is common in scleroderma patients and causes pain, paraesthesia, ulceration, and gangrene. Botulinum toxin A (Btx-A), injected via a palmar approach, has been shown to be effective in the treatment of severe RP. However, hand weakness is a common complication, with rates as high as 27% and can last for up to 6 months (1–5). Objectives: This study aimed to determine the effect of Btx-A injected via a dorsal approach, on hand function and improvement in symptoms, in patients with RP secondary to Scleroderma. Methods: Twenty one patients diagnosed with RP secondary to scleroderma were included. All patients met the criteria for systemic sclerosis of the American College of Rheumatology. They were treated with 10 units of Btx-A, injected into the hand via a dorsal approach. Each patient had a baseline hand assessment and thermographic image (FLIR E60bx). Hand assessment included pinch and power grip strength measurements (Jammar plus digital pinch gauge and dynameter), range of movement of each joint in the hands using a goniometer, Kapandji thumb opposition test and a pain score using the 0–10 visual analogue scale. Patients were asked to report any symptoms of pain, colour change, cold intolerance and complete a Disabilities of the Arm, Shoulder and Hand (DASH) score. Post injection, the hand assessment and thermography was performed at 15 minutes and at 6 weeks in a temperature controlled room at 23.7±2°C. Patients were followed up for 6 weeks and filled out a daily Raynaud's attack diary. Results: 89% of patient reported an overall improvement in symptoms. There was a reduction in the overall number and severity of Raynaud's attacks. There was a significant improvement in both the DASH score value (P=0.008) and Kapandji score value (p=0.007). Pain score decreased by 1 point on average, from 4.9 to 3.9. No patients reported hand weakness as a complication. One patient reported pain at the site of injection for 3 days and 1 patient reported itching for the first 2 days. The effect on range of movement and blood flow was variable. Conclusions: Btx-A injected via a dorsal approach improves symptoms reduces number of attacks in patients with RP secondary to scleroderma. This approach has lower rates of Btx-A related complications compared to the palmar approach. References: Sycha T, et al. European Journal of Clinical Investigation. 2004;34(4):312–3. Neumeister MW et al. Plastic and reconstructive surgery. 2009;124(1):191–201. Uppal L, et al. Journal of Hand Surgery (European Volume). 2013:1753193413516242. Fregene A, et al. Journal of Hand Surgery-American Volume. 2009;34A(3):446–52. Van Beek AL, et al. Plastic and reconstructive surgery. 2007;119(1):217–26. Acknowledgement: We would like to thank Rebecca Canny for her contribution to this project. Disclosure of Interest: None declared